Periostitis Ossificans: Report of Two Cases Resolved with Endodontic Treatment - Hana Bougatef; Eya Moussaoui; Ines Kallel; Mahmoud Smaoui; Lamia Oualha; Nabiha Douki (Case Reports in Dentistry)
Periostitis ossificans is a chronic disease characterized by an ossifying periostitis, occurring in children and young adults, commonly as a reaction to a mild infection or irritation. It is also characterized by the presence of lamellae of newly formed periosteal bone outside the cortex, giving the characteristic radiographic appearance of “onion skin.” Aim. The aim of this paper was to present the clinical and radiographic findings, as well as the postoperative follow-up of two cases diagnosed with periostitis ossificans of dental origin, and to discuss the differential diagnosis and treatment modalities. Case Reports. In the first case, a 16-year-old adolescent was referred for a persistent mandibular swelling. Intraoral examination showed two sinus tracts in relation to the carious necrotic left mandibular first molar. The periapical radiograph showed a periapical lesion in relation to the two root canals of the left mandibular first molar. Occlusal radiographs revealed the “onion skin” bone formation aspect. In the second case, a 10-year-old girl presented to our department with a slightly painful mandibular swelling. The periapical radiograph showed a periapical lesion in relation to both the mesial and distal roots of the carious necrotic right mandibular first molar. Cone beam computed tomography (CBCT) showed a subperiosteal bone formation with an “onion skin” aspect. Diagnosis of periostitis ossificans in the two cases was confirmed and the lesion was resolved by simply an endodontic treatment. Conclusion. Specific attention should be given to clinical and radiographic exploration in case of children with mandibular swelling. As osteosarcoma can be misdiagnosed, additional examinations, such as computed tomography, can be useful in differential diagnosis and in searching malignancy signs.